The Adaptation of Madurese Local Culture in The Translation of Tarbiyatus Shibyan - Inayatur Rosyidah; Zeid B. Smeer; Abdullah Ubaid; Jumriyah Jumriyah (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2026)
This study explores the adaptation of Madurese local culture in the translation of Tarbiyatus Shibyan by K.H. Muhammad Habibullah Ra’is, specifically focusing on the chapter Adab al-Ta‘allum (Ethics of Students in Seeking Knowledge). The research addresses the limited scholarly attention to how regional languages, particularly Madurese, serve as cultural mediators in translating classical Islamic texts used in pesantren (Islamic boarding schools). This gap highlights the need to understand translation not only as linguistic transfer but also as a process of cultural and educational transmission. Employing a descriptive qualitative method, the study applies content analysis to examine the Arabic source text and its Madurese translation. The findings reveal that the translation process adopts a communicative and contextual approach that reflects the integration of Islamic educational values with Madurese cultural expressions. The use of local idioms and moral expressions effectively strengthens students’ ethical awareness, respect, and spiritual responsibility. Moreover, the translation demonstrates that local languages function as cultural bridges in sustaining religious education and preserving local wisdom within the Islamic boarding schools tradition.